Factors Influencing Neonatal Mortality Rate in High-Risk Hospital Settings - Saha, Liton Chandra; Saha, Rinky Rani; Jahan, Nishat; Rahman, Maksudur; Hoque, Mahbubul; Shirin, Mahfuza; Hossain, M Monir (Northern International Medical College Journal, 2025)
Background: Neonatal mortality remains a significant public health concern in low-resource, hospital settings. Objective: This study aimed to investigate factors influencing neonatal mortality in a tertiary care hospital in Bangladesh, focusing on demographic, maternal, and clinical characteristics associated with neonatal outcomes. Methods: This retrospective study was conducted over one year (January to December 2022) at Bangladesh Shishu Hospital and Institute, involving 2,700 high-risk neonates admitted to the SCABU 1 and SCABU 2. Among these, 216 neonates (8%) died. Data on demographic information, clinical diagnoses, and maternal health factors were collected from hospital records, with statistical analyses performed to identify key mortality risk factors. Results: The primary causes of neonatal mortality were prematurity with its complications (43.98%), sepsis (22.22%), and perinatal asphyxia (10.19%), with 25% of neonates classified as extremely low birth weight (ELBW) (<1000g). Maternal factors included high rates of hypertension (37.04%) and inadequate antenatal care, with only 25% of mothers having regular ANC. Cesarean section was the predominant delivery method (62.96%), particularly in preterm births (74.07%). Conclusions: High neonatal mortality in this cohort was strongly associated with respiratory distress syndrome (RDS), infections, and prematurity, exacerbated by maternal comorbidities and inadequate antenatal care. Improving prenatal and neonatal care resources, infection control, and support for high-risk pregnancies is crucial to reducing mortality rates in similar hospital settings. Northern International Medical College Journal Vol. 14 No. 1-2 July 2022-January 2023, Page 633-638